Enriched dairy fat matrix diet prevents early life lipopolysaccharide-induced spatial memory impairment at adulthood. (October 2016) - Dinel, A.L.; Rey, C.; Baudry, C.; Fressange-Mazda, C.; Le Ruyet, P.; Nadjar, A.; Pallet, P.; Joffre, C.; Layé, S.
Abstract: Polyunsaturated fatty acids (PUFAs) are essential fatty acids, which are critical for brain development and later life cognitive functions. The main brain PUFAs are docosahexaenoic acid (DHA) for the n-3 family and arachidonic acid (ARA) for the n-6 family, which are provided to the post-natal brain by breast milk or infant formula. Recently, the use of dairy lipids (DL) in replacement of vegetable lipids (VL) was revealed to potently promote the accretion of DHA in the developing brain. Brain DHA, in addition to be a key component of brain development, display potent anti-inflammatory activities, which protect the brain from adverse inflammatory events. In this work, we evaluated the protective effect of partial replacement of VL by DL, supplemented or not with DHA and ARA, on post-natal inflammation and its consequence on memory. Mice were fed with diets poor in vegetal n-3 PUFA (Def VL), balanced in vegetal n-3/n-6 PUFA (Bal VL), balanced in dairy lipids (Bal DL) or enriched in DHA and ARA (Supp VL; Supp DL) from the first day of gestation until adulthood. At post-natal day 14 (PND14), pups received a single administration of the endotoxin lipopolysaccharide (LPS) and brain cytokine expression, microglia phenotype and neurogenesis were measured. In a second set of experiments, memory and neurogenesis were measured at adulthood. Overall, our data showed that lipid quality of the diet modulates early life LPS effect on microglia phenotype, brain cytokine expression and neurogenesis at PND14 and memory at adulthood. In particular, Bal DL diet protects from the adverse effect of early life LPS exposure on PND14 neurogenesis and adult spatial memory. Highlights: The importance of dairy lipids for DHA accretion in the developing brain. That the quality of lipids in the diet impacts brain neuroplasticity. That the quality of lipids protects from the cognitive effect of PND14 LPS exposure.